Pandangan Ulama NU Kabupaten Lamongan Terhadap Penggunaan Intra Uterine Device (IUD) dalam Keluarga Berencana - Mahbubah, Lathifatul (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2015)
This study discusses the outlook of the Muslim scholars of NU (Muslim scholar renaissance) of Lamongan in the maqasid al-shari'ah perspective to the use of Intra Uterine Device (IUD) in Family Planning program. The data are obtained through interview with a number of the Muslim scholars of NU of Lamongan. They are then analyzed qualitatively with descriptive technique and deductive mindset. The study concludes that the Intra Uterine Device (IUD) is a contraceptive device used by a woman by inserting it into her uterus. As for the model, there are various forms such as like a spiral, wing, letter